The Effect of Oral Albumin Intake on Serum Albumin Levels in Preeclamsia Patients With Hypoalbuminemia in RSUP Dr. M. Djamil Padang - Irwin Fitriansyah; Dovy Djanas; Hafni Bachtiar (Andalas Obstetrics And Gynecology Journal, 2021)
Introduction : Albumin main function is maintaining the plasma colloid oncotic pressure. Preeclampsia cause a decrease in serum albumin in the pregnant woman. Low albumin levels increase mortality, longer wound healing and longer hospital stays. The intake of oral albumin is expected to be effective in increasing the level of albumin in the blood.Objective : To determine the effect of freeze dryer method intake compared to liquid snakehead fish extract in patients with preeclampsia and hypoalbuminemia.Material and methods : Using pre and post-test control group design.The total sample was 38 patients with severe preeclampsia with hypoalbuminemia, divided into control and intervention groups. Control was given the intake of liquid snakehead fish extract, in the intervention was given the Freeze dryer method. The research data were analyzed using the Mann Whitney test method and the Wilcoxon test.Results : In the intervention group the mean pretest albumin level was 2.66 ± 0.17 gr / dl and on the 4th day it was 3.13 ± 0.16 gr / dl (p = 0.000). In the control group the mean pretest albumin level was 2.72 ± 0.15 gr / dl and on the 4th day it became 3.06 ± 0.14 gr / dl (p = 0.000). On the 4th day after treatment, the increase in serum albumin levels in the intervention group was 0.47 ± 0.19 gr / dl; whereas in the control group was 0.34 ± 0.10 gr / dl with a value of p = 0.031 (p <0.05).Conclusion : The freeze dryer method (freeze dryer method ) for the Cork Fish Extract resulted in a higher increase in albumin levels than the liquid snakehead fish extract.Keywords: Preeclampsia, Hypoalbuminemia, freeze dryer method of Snakehead Fish Extract